Good institutions and tax revenue outcomes in resource-rich countries: When "good" is not enough - Daniel Chachu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Developing countries that experience commodity booms struggle to mobilize sustainable tax revenues. Emerging literature on the subject notwithstanding, there is limited exploration of the specific types of institutions critical for improving fiscal capacity in resourcerich contexts. This paper investigates which types of institutions moderate the adverse effect of natural resource rents on non-resource tax effort. I propose a simple theoretical model and complement its insights with an empirical examination of the mediating role of 12 different measures of institutional quality commonly used in the literature. I find evidence of a mitigating role for 'constraints on executive power' and 'democracy'. Other covariates found to be important are national income per capita, the size of the agricultural sector, and control of corruption. The results suggest that effort to bolster sustainable tax effort in resource-rich contexts must focus not only on building effective political institutions but also on addressing structural constraints.
Keywords: Q32; H71; P48; Q01; 330; natural resource rents; non-resource tax revenue; institutions; sustainability; democracy